2019
DOI: 10.1038/s41389-019-0152-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGFβ3-Smads-Sp1 axis in DcR3-mediated immune escape of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of tumour-associated mortality worldwide, but no significant improvement in treating HCC has been reported with currently available systemic therapies. Immunotherapy represents a new frontier in tumour therapy. Therefore, the immunobiology of hepatocarcinoma has been under intensive investigation. Decoy receptor 3 (DcR3), a member of the tumour necrosis factor receptor (TNFR) superfamily, is an immune suppressor associated with tumourigenesis and cancer metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Every year, the government has provided millions of money to the studies of HCC, and sorafenib and regorafenib have made great contributions for the therapy of HCC. What's more, many studies have focused the mechanisms of HCC progression and metastasis [26][27][28][29]. Our study based on the clinical samples databases, and identified a new pathway connected to the progression of HCC, is another sample to study HCC progression for better therapy of HCC patients.…”
Section: Discussionmentioning
confidence: 93%
“…Every year, the government has provided millions of money to the studies of HCC, and sorafenib and regorafenib have made great contributions for the therapy of HCC. What's more, many studies have focused the mechanisms of HCC progression and metastasis [26][27][28][29]. Our study based on the clinical samples databases, and identified a new pathway connected to the progression of HCC, is another sample to study HCC progression for better therapy of HCC patients.…”
Section: Discussionmentioning
confidence: 93%
“…TGF-β1 activates fibroblasts and transforms them into myofibroblasts (2,3). Numerous studies reported that TGF-β1 is a key fibrogenic factor, which can induce EMT in PF (27). Subsequently, inhibition of EMT through the TGF-β1 pathway may be considered as a potential therapeutic option for IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Chaoul et al (2020) CD4+T cell The immune mechanism Knockdown of DCR3 expression in HCC significantly restored the immunity of CD4+T cells. Inhibition of DCR3 expression may provide a novel immunotherapy approach to restore immunity in HCC patients Zhu et al (2019) CD4+T cell The immune mechanism Activated CD4+T cells from HCC stimulate macrophages to produce C-X-C motif chemokine 10(CXCL10). CXCL10 binds to the CXC chemokine receptor 3 on B cells and signals them through extracellular signal-regulated kinases, making them plasma cells that produce IgG.…”
Section: Dhanasekaran Et Al (2020) Cd4+t Cell the Immune Mechanismmentioning
confidence: 99%